Changes of Phenotypic Pattern in Functional Movement Disorders: A Prospective Cohort Study - Tomić, Aleksandra; Ječmenica Lukić, Milica; Petrović, Igor; Svetel, Marina; Dragašević Mišković, Nataša; Kresojević, Nikola; Marković, Vladana; Kostić, Vladimir S. (Frontiers in Neurology, 2020)
IIntroduction: Functional movement disorders (FMD) refer to a group of movement disorders that present with clinical characteristics incongruent to those due to established pathophysiologic processes, as for example in the case of neurodegeneration or lesions. The aim of this study was to assess clinical features that contribute to the specific phenotypic presentations and disease course of FMD. Methods: The study consisted of 100 patients with FMD treated at Clinic for Neurology, Clinical Centre of Serbia, who were longitudinally observed. Comprehensive clinical and psychiatric assessment was performed at the baseline, when initial FMD phenotype was defined. Follow-up assessment of phenotypic pattern over the time and clinical course was done after 3.2±2.5 years at average. Results: We showed that 48% of FMD patients were prone to changes of phenotypic pattern during the disease course. Dystonia had tendency to remains as single and unchanged phenotype over the time (68.2%), while patients initially presented with Tremor, Gait disorder, Parkinsonism and Mixed phenotype were more susceptible to developing additional symptoms (62.5%, 50%, 100% and 100%, respectively). Higher levels of somatoform experiences (p=0.033, Exp(B)=1.082) and higher motor severity (p=0.040, Exp(B)=1.082) at baseline assessment were associated with an increased likelihood of further enriching of FMD phenotype with additional functional symptoms. Also, these patients more frequently reported pain, and had higher scores on majority of applied psychiatric scales, together with more frequent presence of major depressive disorder. Conclusion: Results from this prospective study suggested tendency for progression and enrichment of functional symptoms in FMD patients over time. Besides functional core symptoms, other key psychological and physical features (like pain or multiple somatisations) were quite relevant for chronicity and significant dysability of FMD patients.